Is justice as fairness a realistic utopia? A critical examination of Rawls's idea of overlapping consensus. - Maria Paz C Felton (2006)
The purpose of this thesis is to develop an alternative account of how justice as fairness can be delivered. My general proposition is that if justice as fairness is to be regarded as a realistic utopia, some alterations need to be made into the argument about the possibilities of its realization offered by Rawls. The main problem comes from the idea of overlapping consensus and its association with stability. A crucial working conjecture is that we need overlapping consensus neither to stabilize justice as fairness, nor to justify it. My alterations to Rawls's argument also originate as a result of two theoretical burdens within political liberalism: its notion of stability and its account of the fact of reasonable pluralism. Both ideas have been inadequately problematized, and therefore demand significant revision. The idea of stability needs to be revised because of its exclusive focus on questions of moral coherence at the expense of more relevant aspects such as institutional and political stability. The account of reasonable pluralism also needs to be revised because it is both too narrow and significantly unfocused. A crucial consequence that follows from these revisions is that, in order to preserve institutional stability under the conditions of pluralism, we need to render the stability of institutions separately from the coherence of citizens' overall moralities. These two conceptual revisions lead me to effect three alterations into Rawls's argument. In particular I show that: 1) constitutional consensus is necessary, but not yet sufficient, for stability of the required kind, 2) political justification is necessary and sufficient for the right kind of justification, and 3) overlapping consensus is part of moral, not political, justification and, therefore, not required for a political project such as Rawls's.